The Effectiveness of Reminiscence Therapy in Improving Elderly’s Well-Being - Firdaus, Etty Sabariah; Widyarini, Nilam; Mustika, Martina Dwi (Bina Nusantara University, 2019)
The research discussed Subjective well-being (SWB) with reminiscence therapy in the elderly. This research used a single-case experiment design to examine the effectiveness of reminiscence therapy in improving the well-being of active, elderly aged 70 years old and over. There were two participants in this research, one male and one female. This intervention consisted of five meetings held once a week for ±90 minutes each session. Quantitative analysis using the Oxford Happiness Questionnaire and qualitative analysis through observation and interviews showed an improvement in participants? subjective well-being following the intervention. Therefore, the results of this research are likely that reminiscence therapy is effective in improving the subjective well-being of elderly individuals.